2019
DOI: 10.3390/geosciences9030113
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Tsunami Risk to Residential Buildings at Omaha Beach, New Zealand

Abstract: Coastal settlements worldwide have suffered significant damage and loss to tsunami hazards in the last few decades. This period coincides with socio-economic changes that have heightened spatio-temporal risk through increased coastal development and infrastructure. In this study, we apply a spatio-temporal loss model to quantify the changes in direct economic losses to residential buildings from tsunami hazards over a 20-year period in Omaha Beach, New Zealand. The approach reconstructed temporal urban settlem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Savaii has a slightly greater proportion of buildings within the tsunami evacuation zones (51%) compared to Hazard layers depicting maximum extent and flow depths at 50 and 10 m grid resolution [14] and evacuation zones [20] are combined with exposure layers (distribution of buildings and road features in districts and villages) to enumerate the sum of the exposed features. The RiskScape analysis framework is described by [22] and has been previously demonstrated in several inundation-related impacts and exposure analyses (e.g., [6,19,46]).…”
Section: National Building and Road Exposurementioning
confidence: 99%
“…Savaii has a slightly greater proportion of buildings within the tsunami evacuation zones (51%) compared to Hazard layers depicting maximum extent and flow depths at 50 and 10 m grid resolution [14] and evacuation zones [20] are combined with exposure layers (distribution of buildings and road features in districts and villages) to enumerate the sum of the exposed features. The RiskScape analysis framework is described by [22] and has been previously demonstrated in several inundation-related impacts and exposure analyses (e.g., [6,19,46]).…”
Section: National Building and Road Exposurementioning
confidence: 99%
“…Exposure mapping was undertaken by using the RiskScape multi-hazard risk model framework [53]. This modular framework is configured to produce exposure and impact data by analyzing hazard data and the characteristics of the assets at risk, and it has been applied in exposure studies in New Zealand and the wider Pacific region [54][55][56][57][58]. The RiskScape engine computes user-defined risk/exposure/vulnerability calculations for these hazards and assets.…”
Section: Exposure Analysismentioning
confidence: 99%
“…Previous research has identified several coastal sites within the Auckland region that have evidence of past marine inundation attributed to tsunamis (Figure 1; Nichol et al 2003Nichol et al , 2007De Lange and Moon 2007) and Goff et al (2005) collated evidence for five paleotsunamis affecting the Auckland region in the past ∼2600 years. While a number of probabilistic tsunami hazard and risk studies for the Auckland region have been undertaken recently (Lane et al 2013;Power et al 2013Power et al , 2017Paulick et al 2019), the paleotsunami question has not been revisited since the 2005 report by Goff et al…”
Section: Introductionmentioning
confidence: 99%